Developing a Learning Hybrid NoSql Algorithm for Vehicle Routing Problem - Ozdemir, Rustu Hilmi; Sertbas, Ahmet (2023 8th International Conference on Computer Science and Engineering (UBMK), 2023)
In this study, a learning Vehicle Routing Algorithm was developed to optimize the delivery of the products in the warehouses located in one or more central locations to the customers in various locations using a certain number of vehicles, and the return of the vehicles to the warehouse/home, and the results were compared with other algorithms used in the literature in terms of accuracy and time performance. A hybrid algorithm that works on a hierarchical database has been developed for the distribution of multiple locations according to the Time Intervals, Types, In-Route Constraints, Optimization Purposes, Road Structure, Fleet Structure and Layout, Inter-Route Constraints. Past plans help to create new plans. New plans are versions of old plans adapted to the new situation. This process is called "learning by planning". 25% increase in accuracy and 97% increase in time performance was observed.